Beyond Born-Oppenheimer approximation in ultracold atomic collisions - Eberhard Tiemann; Philipp Gersema; Kai K. Voges; Torsten Hartmann; Alessandro Zenesini; Silke Ospelkaus (Physical Review Research, 2020)
We report on deviations beyond the Born-Oppenheimer approximation in potassium interatomic potentials. Identifying three previously unknown d-wave Feshbach resonances, we significantly improve the understanding of the ^{39}K interatomic potentials. Combining these observations with the most recent data on known inter- and intraisotope Feshbach resonances, we show that Born-Oppenheimer corrections can be determined from atomic collisional properties alone and that significant differences between the homo- and heteronuclear cases appear.